Leverage menjadi bagian penting dalam pengambilan keputusan keuangan - Faizal Faizal; Muh Mulawarman JR; Andayani Andayani; Mahadir Muhammad Abdul Kadir; Miftahul Jannah Ilyas; Mucriana muchran (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2026)
Leverage is one of the essential aspects of financial management that enables companies to obtain funding through debt to finance operational activities and investment projects. Proper use of leverage can improve profitability, optimize capital structure, and enhance firm value. However, excessive leverage may increase financial risks, including financial distress and potential bankruptcy. This study aims to analyze the role of leverage in financial decision-making, its benefits, and the risks associated with its implementation. The research employs a descriptive qualitative method using a library research approach by reviewing relevant books, scientific journals, and academic literature. The findings indicate that leverage has a significant influence on financing decisions, capital structure, profitability, and firm value. Optimal leverage can improve a company's financial performance when supported by effective debt management and sufficient cash flow generation. Therefore, companies should carefully consider their financial condition, interest rates, business risks, and growth prospects before determining their leverage policy.